Differential role of Interleukin-1 and Interleukin-6 in K-Ras-driven pancreatic carcinoma undergoing mesenchymal transition. (1st February 2018) - Siddiqui, Imran; Erreni, Marco; Kamal, Mohammad Azhar; Porta, Chiara; Marchesi, Federica; Pesce, Samantha; Pasqualini, Fabio; Schiarea, Silvia; Chiabrando, Chiara; Mantovani, Alberto; Allavena, Paola
ABSTRACT: K-Ras mutations are a hallmark of human pancreatic adenocarcinoma (PDAC) and epithelial-mesenchymal-transition (EMT) is a driver of progression. Oncogenic K-Ras causes the constitutive activation of NF-kB and the switch-on of an inflammatory program, which further fuels NF-kB and STAT3 activation. In this study we investigated how inflammatory pathways triggered by oncogenic K-Ras are regulated in human pancreatic cancer cells with distict epithelial or mesenchymal phenotype. Our results demonstrate that in cells with epithelial features, K-Ras driven inflammation is under the control of IL-1, while in cells undergoing EMT, is IL-1 independent. In pancreatic tumor cells with EMT phenotype, treatment with IL-1R antagonist (Anakinra) did not inhibit inflammatory cytokine production and tumor growth in mice. In these cells IL-6 is actively transcribed by the EMT transcription factor TWIST. Targeting of mesenchymal pancreatic tumors in vivo with anti-IL-6RmAb (RoActemra) successfully decreased tumor growth in immunodeficient mice, inhibited the inflammatory stroma and NF-kB-p65 and STAT3 phosphorylation in cancer cells. The results confirm that IL-1 is an important driver of inflammation in epithelial pancreatic tumors; however, tumor cells undergoing EMT will likely escape IL-1R inhibition, as IL-6 is continuously transcribed by TWIST. These findings have implications for the rational targeting of inflammatory pathways in human pancreatic cancer.